Peningkatan Produksi dan Protein Kedelai dengan Aplikasi Bokasi dan Rhizo-Plus di Lahan Podsolik Merah Kuning - Ratna Dewi (Jurnal Penelitian Pertanian Terapan, 2011)
Efforts to increase production and soy protein are often constrained by the condition of land that are sour that cause failure in the form of nodules which is the organ to tie up nitrogen air. Fermented organic material which is fermented by microorganisms Efectif useful to enrich the soil, while the rhizo-plus is a useful microbe fertilizers increase the yield through the appropriate rhizobium strains. Microorganisms contained in the fermented and rhizo-plus to increase the supply of the element of N and P for plants. This study aims to determine the influence of fermented and rhizo-plus in increasing production and protein content of soybeans. Treatments consisted of a single factor that is prepared in a randomized group design Perfect .The treatments were: chemical fertilizer application (A1), the application rhizo-plus +1 / 2 SP36 + KCl (A2), fermented application (A3), and the application of fermented + rhizo-plus (A4). Each treatment was repeated three times. Data were analyzed with ANOVA and if there are differences in the median value of treatment followed by Least Significant Difference test (LSD), each at level 5%. Results showed the application fermented and rhizo-plus did not affect significantly to the number of branches per plant, number of books per plant and number of nodules per plant. Applications fermented in combination with rhizo-plus (A4) gives results of seeds per plant and per plot is more severe compared with other treatments ie weighing 32.39 g per plant and 6:48 kg per plot. While the application of chemical fertilizers alone (A1), Rhizo-plus + Â½ SP-36 + KCl (A2), and fermented (A3), not significantly different, ie, each weighing 4.68 kg and g 23:39, 21:27 and 4:25 g kg; 27.68 g and 4.68 kg. Applications rhizo-plus +1 / 2 SP36 + KCl on soybean plants (A2) has a higher soy protein content compared with other treatments which is equal to 28.21%, while the other applications in a row A1 = 26.22%, A3 = 25.60%; and A4 = 26.92%. Protein content of the results of this research is still relatively low compared with soy in general description. Keywords: Production, Soybean Protein, Bokasi and Rhizo-plus